High luminescent brightness and thermal stability of red emitting Li3Ba2Y3(WO4)8:Eu3+ phosphor. Issue 12 (September 2016) - Wang, Lei; Guo, Wenlei; Tian, Yue; Huang, Ping; Shi, Qiufeng; Cui, Cai'e
Abstract: A series of Li3 Ba2 Y3− x (WO4 )8 : x Eu 3+ ( x =0.1, 1, 1.5, 2 and 2.8) phosphors were synthesized by a high temperature solid-state reaction method. Under the excitation of near ultraviolet (NUV) light, the as-prepared phosphor exhibits intense red luminescence originating from the characteristic transitions of Eu 3+ ions, which is 1.8 times as strong as the commercial Y2 O2 S:Eu 3+ phosphor. The optimal doping concentration of Eu 3+ ions here is confirmed as x =1.5. The electric dipole-quadrupole (D-Q) interaction is deduced to be responsible for concentration quenching of Eu 3+ ions in the Li3 Ba2 Y3 (WO4 )8 phosphor. The analysis of optical transition and Huang-Rhys factor reveals a weak electron-phonon coupling interaction. The temperature-dependent emission spectra also indicate that the as-prepared Li3 Ba2 Y3 (WO4 )8 :Eu 3+ phosphor has better thermal stability than that of the commercial Y2 O2 S:Eu 3+ phosphor. Therefore, our results show that the as-prepared Li3 Ba2 Y3 (WO4 )8 :Eu 3+ phosphor is a promising candidate as red emitting component for white light emitting diodes (LEDs).